Obravnavanje bolnikov z možgansko kapjo na terenu - Švigelj, Viktor (Medicinski razgledi, 2002)
Acute stroke is increasingly recognized as one of the leading factors of morbidity and mortality in adult worldwide population, with a mortality rate in the acute stage of more than 20%. Ischemic stroke is by far the most frequent subtype of acute stroke (> 80%). Successful stroke management begins by recognizing stroke as a medical emergency, such as acute myocardial infarction or severe trauma and, even more importantly, recognizing that a patient presenting as a medical emergency has had a stroke. Initial evaluationof stroke patients includes assessment of breathing and circulation.Neurological assessment can also be performed when the patient is first seen and, if necessary, therapeutic measures can be instituted. The goalis to ascertain the severity and type of neurological impairment. The differential diagnoses which should be considered include coma of another origin, trauma, drug overdose; post-seizure states or metabolic disorders. Effective treatment of patients who have sustained an acute ischemic stroke requires rapid assessment and early intervention. The window of opportunity for thrombolytic therapy is limited to the first few hours after the onset of stroke. In all other types of cerebrovascular incidents, such as intracerebralbleeding, posttraumatic hemorrhage and subarachnoid hemorrhage, hospital management is also mandatory.
Keywords: Cerebrovascular Disorders; Cerebrovaskularne motnje; Emergency Medical Services; Možganski infarkt; Trombolitično zdravljenje; Cerebral Ischemia; Thrombolytic Therapy; Urgentne, medicinske službe; Možganska krvavitev; Cerebral Infarction; Subarachnoid Hemorrhage; Subarahnoidna krvavitev; Cerebral Hemorrhage; možganska kap; diagnostika; urgentna medicina